Lesser living creatures of the Renaissance. - Botelho, Keith; Botelho, Keith; Campana, Joseph; Campana, Joseph; Cole, Lucinda; Dolan, Frances E.; Duckert, Lowell; Fleck, Andrew; Laroche, Rebecca; Munroe, Jennifer; Tigner, Amy L.; Wolfe, Jessica Lynn; et al. (Animalibus: Of Animals and Cultures, 2023)
Lesser Living Creatures examines literary and cultural texts from early modern England in order to understand how people in that era thought about--and with--insect and arachnid life. The conversations in this two-volume set address the collaborative, multigenerational research that produced early modern natural history and provide new insights into the old question of what it means to be human in a world populated by beasts large and small.Volume 2, Concepts, explores ideas that cut across species, insect and otherwise, both building on and invigorating critical vocabularies developed over nearly two decades of early modern animal studies. The contributors explore topics such as the medical and culinary consumption of insects; extermination campaigns; the auditory and emotive effects of a swarm; insects and politics; and notions of infestation, stinging, and creeping. Throughout, they illuminate how early modern science and literature worked as intersecting systems of knowledge production about the natural world and show definitively how insect life was, and remains, intimately entangled with human life.In addition to the editors, contributors to this volume include Lucinda Cole, Frances E. Dolan, Lowell Duckert, Andrew Fleck, Rebecca Laroche, Jennifer Munroe, Amy L. Tigner, Jessica Lynn Wolfe, Derek Woods, and Julian Yates.